2020
DOI: 10.3390/pathogens9110937
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Ticks and Tick-Borne Pathogens of Small Ruminants in Pakistan

Abstract: Ticks and tick-borne diseases (TTBDis) are a major constraint to the health and production of small ruminants in Pakistan. Despite being the subject of intermittent studies over the past few decades, comprehensive information on the epidemiology and control of TTBDis is lacking. Herein, we have systematically reviewed the current knowledge on TTBDis of small ruminants in Pakistan. Critical appraisal of the selected 71 articles published between 1947 to 2020 revealed that morphological examination had been the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 125 publications
(202 reference statements)
3
13
1
Order By: Relevance
“…Nonetheless, there was some overlap between parasites in Tunisia and Oman, indicating that the separation between the parasite populations in the two countries was incomplete ( Figure 1 B). Similar incomplete separation has been previously reported in T. annulata populations from widely separated countries [ 7 , 20 ]. These observations suggest that despite ecological and epidemiological barriers between the different parasite populations, gene flow occurs between the above countries, probably due to the movement of animals, often as an asymptomatic infection and infesting ticks.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Nonetheless, there was some overlap between parasites in Tunisia and Oman, indicating that the separation between the parasite populations in the two countries was incomplete ( Figure 1 B). Similar incomplete separation has been previously reported in T. annulata populations from widely separated countries [ 7 , 20 ]. These observations suggest that despite ecological and epidemiological barriers between the different parasite populations, gene flow occurs between the above countries, probably due to the movement of animals, often as an asymptomatic infection and infesting ticks.…”
Section: Discussionsupporting
confidence: 88%
“…The parasites in these four countries tend to form genetically distinct groups with some geographical sub-structuring (Figures 1B and 2). The relatively lower level of genetic differentiation detected between T. annulata from Pakistan and Oman (F ST = 0.09) when compared with that observed between Pakistan and Tunisia (F ST = 0.1293) and Pakistan and Turkey (F ST = 0.166), is consistent with the pattern of a high level of differentiation documented between samples of T. annulata from Oman and Tunisia (F ST = 0.06855) and from Oman and Turkey (F ST = 0.1092) [20]. Similar observations regarding the genetic diversity of T. annulata have been reported in a recent study from India by Roy et al [6].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, grooming, which is the manual plucking of ticks by agricultural workers, is a popular practice in Pakistan for tick management ( 63 ). However, only two studies have evaluated the efficiency of acaricidal medicines in vivo , and the authors reported that cypermethrin was the most efficient tick control drug in livestock ( 59 , 64 ). Numerous studies have been conducted to determine the efficiency of different medicines (alone or in combination with antibiotics) in treating ectoparasites, including buparvaquone, diminazene aceturate + imidocarb dipropionate, and oxytetracycline ( 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…In extensively reared goats, tick infestation is identified as a major epidemiological issue, especially in tropical and subtropical regions [16]. A high diversity of hard tick species infesting goats has been reported in Middle East and North Africa [17] and a prevalence of circa (ca.)…”
Section: Introductionmentioning
confidence: 99%